Efektivitas Penegakan Hukum Terhadap Tindak Pidana Pertanahan dalam Perspektif Keadilan Agraria di Indonesia - suhaimi; Erick Sani; Jamatul Firdaus; Gusuy Maharani; Bayu Aji Rekso dipurwo (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2026)
This study analyses the effectiveness of criminal law enforcement in the field of land through the perspective of agrarian justice. The aim is to evaluate the level of effectiveness, identify inhibiting factors, and formulate policy recommendations to strengthen the protection of equitable land rights. The method used is normative law with a legislative, conceptual, and case approach. Primary and secondary data in the form of regulations, doctrines, and jurisprudence were collected through literature studies and analysed qualitatively and prescriptively. The findings show that law enforcement has not been effective. The main obstacles include regulatory disharmony, weaknesses in the land administration and data systems, difficulties in proving cases, and poor coordination between law enforcement agencies. In conclusion, strengthening law enforcement requires: regulatory harmonisation, integration of land databases, capacity building of officials, and the implementation of policies oriented towards the restoration of agrarian rights and justice as a priority in case resolution.